A sustainable process to recycle aluminum from coal fly ash for simultaneous removal of iron: Solid waste management and evaluation. (30th June 2022) - Li, Xiang; Ma, Baozhong; Wang, Chengyan; Chen, Yongqiang; Yang, Weijiao; Zhang, Wenjuan
Graphical abstract: Highlights: An effective process for recovering Al from solid waste (CFA) was developed. Thermodynamics of the leaching process in a nitric acid system was analysed. Al was leached selectively but with very low solubilization of Fe. Abstract: Coal fly ash (CFA) is one of the largest forms of global industrial waste, and continuous accumulation of CFA puts great pressure and poses potential risks to the natural environment. The objective of this study was to evaluate a sustainable process to recycle valuable elements in high-alumina coal fly ash (HACFA). In this study, an efficient and applicable approach was developed to recover Al selectively from HACFA, while most Fe recovery and removal were realized simultaneously in the leaching process. First, the thermodynamic stability of HACFA and the feasibility of Al leaching in HACFA were calculated. Then, HACFA was subjected to nitric acid pressure leaching to selectively extract Al. Under the optimal conditions (temperature of 220 °C, nitric acid concentration of 300 g/L, liquid-to- solid ratio of 4 mL/g, and duration of 2 h), 84.24% of the Al was extracted, and the leaching rate of Fe was 6.67%. The concentrations of Al and Fe in the leachate were 46.34 g/L and 0.52 g/L, respectively. The separation of Al and Fe was completed in the leaching process. The leach liquor was purified to further remove impurities, and Al2 O3 was obtained after crystallization and pyrolysis of the aluminum-rich leachate. Leach residue was mainly composed of silica and Fe2 O3 . This process provides a feasible method for the recovery and utilization of valuable components in HACFA.